Lithofacies and Sedimentation of Organic Matter in Fine Grained Rocks of Nanggulan Formation in Kulon Progo, Yogyakarta - Donatus Hendra Amijaya; Najibatul Adibah; Ahmad Z.A. Ansory (Journal of Applied Geology, 2016)
Fine grained rocks especially shale play a significant role in shale hydrocarbon system. Research on Eocene Nanggulan shale becomes an interest lately since this shale is considered as prospective interval for shale gas source. It potentially contains significant organic matter because coaly sediment is found in this formation as well. Nanggulan Formation fine grained rocks was deposited in various depositional environment from estuary – shallow marine. This paper integrates the result of lithofacies and depositional environment analysis with organic geochemical data to understand the sedimentation process of organic matter. Samples were taken from cores. The result of 14 geochemically analysed samples shows Total Organic Carbon (TOC) content between 0.36–1.00 % for fin e grained rocks (shales) and 12.80 % for coaly shales. Nine samples are categorized as fair and 2 samples are categorized as good source rock. The depositional environment of Nanggulan Formation sediment, which was shallow marine at Late Eocene and estuary (salt marsh) at Early Eocene, produced sediment with higher TOC. Whereas the deposition of sediment in estuary (tidal flat) at Middle Eocene produced lower content of TOC. Vulcanic activity at Middle Eocene also caused less organic material preservation because it produced abundant inorganic material.